Relationships between Serum Biomarkers of Oxidative Stress and Tobacco Smoke Exposure in Patients with Mental Disorders - Ana-Maria Vlasceanu; Daniela Gradinaru; Miriana Stan; Viorela G. Nitescu; Daniela Luiza Baconi (MDPI AG, 2023)
The role of cigarette smoking as an aggravating factor of systemic oxidative stress in patients with mental disorders has not been extensively investigated, although significantly higher rates of smoking are recorded in these subjects in comparison with the general population. In the present study, we tested the hypothesis that smoking might be an exacerbator of systemic oxidative stress, being directly correlated with the degree of exposure to tobacco smoke. We analyzed, in 76 adult subjects from a public health care unit, the relationships between serum cotinine levels as a marker of tobacco smoke exposure, and three biomarkers of oxidative stress: the serum glutathione (GSH), the advanced oxidation protein products (AOPPs), and the total serum antioxidant status (FRAP). The results indicate that the degree of tobacco smoke exposure was inversely associated with GSH levels in both passive and active smokers, suggesting that smoke particulate components' toxicity is associated with a systemic GSH depletion. Paradoxically, the lowest AOPP levels which were positively associated with GSH, were recorded in active smoking patients whereas in passive smokers individual values of AOPPs decreased along with the increase in GSH levels. Our data suggest that an enhanced inhalation of particulate constituents of cigarette smoke could induce critical changes in systemic redox homeostasis and GSH can no longer exert its antioxidant role.